Association of dietary sodium intake with impaired fasting glucose in adult cancer survivors: A population-based cross-sectional study. - Kyuwoong Kim; Hamee Kim; Tae Joon Jun; Young-Hak Kim (PLoS ONE)
Background Dietary sodium intake is a crucial lifestyle factor that should be assessed in adult cancer survivors due to their increased risk of adverse health outcomes compared to the general population. However, its with impaired fasting glucose (IFG) in adult cancer survivors remains unclear. This study aimed to investigate the association of dietary sodium intake categorized by the American Heart Association (AHA) recommendation with IFG in the community-dwelling adult cancer survivors. Methods A total of 1,052 adult cancer survivors without diabetes were identified from the sixth and seventh Korea National Health and Nutrition Examination Survey (KNHANES), 2013-2018. Data on dietary sodium intake was categorized as <1,500 mg/day, 1,500-2,999 mg/day, 2,300-3,999 mg/day, and ≥4,000 mg/day according to the AHA recommendation. A multiple logistic regression model adjusted for demographic, lifestyle, and health status was used to compute odds ratios (OR) and 95% confidence intervals (95% CI) for IFG according to dietary sodium intake categories. Results After adjusting for confounding variables identified in the KNHANES, the adjusted OR among the adult cancer survivors who consumed 1,500-2,999 mg/day, 2,300-3,999 mg/day, and ≥4,000 mg/day of dietary sodium were 1.16 (95% CI: 0.25-5.27), 1.93 (95% CI: 0.40-9.37), and 2.67 (95% CI: 0.59-12.18), respectively, as compared to those who consumed <1,500 mg/day (P value for trend = 0.036). Conclusion Among community-dwelling adult cancer survivors, high dietary sodium intake was marginally associated with increased odds of IFG. Well-designed cohort studies or randomized clinical trials are needed to establish more epidemiologic evidence on this association in adult cancer survivors.